Schemes and Procedures of People’s Business Credit Financing through Murabaha Agreements at Bank Syariah Indonesia Blangpidie - Karmila, Karmila; Mahdani, Said (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research was conducted at Bank Syariah Indonesia (BSI) Blangpidie Branch Office with the objective of exploring the implementation of People’s Business Credit Financing with Murabaha agreements using qualitative research methods. Data collection methods included participant observation and interviews, while data analysis techniques comprised data reduction and inference (validation). The research findings indicate that the application of small financing of KUR (Kredit Usaha Rakyat) financing at Bank Syariah Indonesia Branch Office has the potential to enhance economic growth within the community, particularly for micro, small, and medium-sized enterprises (MSMEs). This, in turn, can stimulate the local economy and assist the community in obtaining capital, contributing not only to the improvement of community welfare but also potentially increasing sales turnover for Bank Syariah Indonesia. The positive outcomes observed in the implementation of People’s Business Credit Financing with Murabaha agreements at Bank Syariah Indonesia Blangpidie Branch Office suggest the potential for broader adoption of Sharia-compliant financing models to support MSMEs. These findings underscore the importance of promoting Islamic financial instruments as a means to stimulate local economies.